As mulheres na diversidade da agricultura familiar:trabalho produtivo, sociabilidade, empoderamento e garantia ao direito fundamental à igualdade - Hoffmann, Glauci Aline (2024)
Patriarchy, closely inserted in family and social relationships throughout the history of humanity, relegated women to a supporting role in said relationships, which was no different in family farming. Through feminist movements, they obtained rights and were inserted into the most diverse social contexts as subjects of their lives and their rights. The UN has established as one of the objectives of sustainable development the eradication of any type of differences between men and women. Despite this, research carried out shows that women are responsible for reproductive and home production work, while men are responsible for productive work, which adds value and guarantees the livelihood of families. For these reasons, the research problem arises: how do women participate in productive activities, become empowered and have their rights enforced in the different productive rationalities [conventional, in transition and unconventional by Basso (2013) adopted by family farmers? Thus, the present research aims to analyze women in the diversity of family farming, focusing on the analysis regarding productive work, empowerment, sociability and guaranteeing the Fundamental Right to Equality. To carry out this research, bibliographical research was used in the initial chapters, in order to deal with fundamental rights, especially the fundamental right to equality, as well as the evolution of women's rights, the role of feminist movements and the contextualization of family farming and its diversity. After qualification, empirical research was carried out observing women in the productive rationalities (conventional; in transition; non-conventional) of families, through the application of a semi-structured questionnaire, with qualitative and quantitative analysis of the results. The research demonstrated that women of unconventional and transitional rationality have effective participation in production processes, as well as that in sociability they relate with a view to improving the production process. Furthermore, women have a feeling of empowerment regarding family life in all rationalities, but in society and production in different ways in each rationality, as well as they do not feel empowered regarding their rights, especially regarding the fundamental right to equality.